Identification of Emergency Department Patients With Acute Heart Failure at Low Risk for 30-Day Adverse Events: The STRATIFY Decision Tool - Collins, Sean P. (JACC Heart Fail, 2015)
OBJECTIVES: No prospectively derived or validated decision tools identify emergency department (ED) patients with acute heart failure (AHF) at low risk for 30-day adverse events who are thus potential candidates for safe ED discharge. This study sought to accomplish that goal. BACKGROUND: The nearly 1 million annual ED visits for AHF are associated with high proportions of admissions and consume significant resources. METHODS: We prospectively enrolled 1,033 patients diagnosed with AHF in the ED from 4 hospitals between July 20, 2007, and February 4, 2011. We used an ordinal outcome hierarchy, defined as the incidence of the most severe adverse event within 30 days of ED evaluation (acute coronary syndrome, coronary revascularization, emergent dialysis, intubation, mechanical cardiac support, cardiopulmonary resuscitation, and death). RESULTS: Of 1,033 patients enrolled, 126 (12%) experienced at least one 30-day adverse event. The decision tool had a C statistic of 0.68 (95% confidence interval: 0.63 to 0.74). Elevated troponin (p < 0.001) and renal function (p = 0.01) were significant predictors of adverse events in our multivariable model, whereas B-type natriuretic peptide (p = 0.09), tachypnea (p = 0.09), and patients undergoing dialysis (p = 0.07) trended toward significance. At risk thresholds of 1%, 3%, and 5%, we found0%, 1.4%, and 13.0%patients were at low risk, with negative predictive values of 100%, 96%, and 93%, respectively. CONCLUSIONS: The STRATIFY decision tool identifies ED patients with AHF who are at low risk for 30-day adverse events and may be candidates for safe ED discharge. After external testing, and perhaps when used as part of a shared decision-making strategy, it may significantly affect disposition strategies. (Improving Heart Failure Risk Stratification in the ED [STRATIFY]; NCT00508638)